Building Character Through Pancasila Values to Sovereign Nation - Martoredjo, Nikodemus Thomas (Humaniora, 2016)
This article discussed the role of character development through the inculcation of the values contained in Pancasila to achieve sovereignty of the nation. Character development became a priority to look at the situation and condition of the nation that appreciation and application of the main values of Pancasila was degraded. Embedding Pancasila values creatively should be implemented in a variety of learning processes both formal and informal. Basic values contained in Pancasila was not only a slogan, but also became the guiding principles in facing all of challenges and threats of the nation. The purpose of this study was to strengthen the resilience of ourselves as a nation. With such resilience, then sovereignty as a great nation can be enforced. The method used in writing this article was literature studies approach. The result of this study is if the values of Pancasila (das sollen) has become daily reality (das Sein), it can build good resistance by itself. Whatever challenges or threats are faced, it will be resolved properly and may even be a stepping-stone to be better.